Pretty Salma : a Little Red Riding Hood story from Africa - Daly, Niki (New York : Scholastic, 2006)
In this version of "Little Red Riding Hood," set in Ghana, a young girl fails to heed Granny's warning about the dangers of talking to strangers.
K
510
K
Keywords: Fairy tales; Folklore